1995
DOI: 10.1523/jneurosci.15-10-06963.1995
|View full text |Cite
|
Sign up to set email alerts
|

Axonal regeneration and physiological activity following transection and immunological disruption of myelin within the hatchling chick spinal cord

Abstract: Transections of the chicken spinal cord after the developmental onset of myelination at embryonic day (E) 13 results in little or no functional regeneration. However, intraspinal injection of serum complement proteins with complement-binding GalC or 04 antibodies between E9-E12 results in a delay of the onset of myelination until E17. A subsequent transection of the spinal cord as late as E15 (i.e., during the normal restrictive period for repair) results in neuroanatomical regeneration and functional recovery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
43
0

Year Published

1997
1997
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(44 citation statements)
references
References 35 publications
1
43
0
Order By: Relevance
“…We have used a complement-fixing antibody to galactocerebroside (GalC), coadministered intraspinally with serum complement, to achieve transient focal demyelination at the site of SCI. [67][68][69] Within the CNS, GalC is restricted to the cell membrane of oligodendrocytes and myelin; specifically, it is present in the outer layer of the myelin membrane. Binding of the GalC antibody triggers activation of the complement cascade, which results in disruption of myelin membranes and recruitment of endogenous microglia or invading macrophages to phagocytically clear CNS myelin within the injured region.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 99%
“…We have used a complement-fixing antibody to galactocerebroside (GalC), coadministered intraspinally with serum complement, to achieve transient focal demyelination at the site of SCI. [67][68][69] Within the CNS, GalC is restricted to the cell membrane of oligodendrocytes and myelin; specifically, it is present in the outer layer of the myelin membrane. Binding of the GalC antibody triggers activation of the complement cascade, which results in disruption of myelin membranes and recruitment of endogenous microglia or invading macrophages to phagocytically clear CNS myelin within the injured region.…”
Section: Myelin and Myelin Signaling: An Inhibitory Chorus Linementioning
confidence: 99%
“…Recent studies have shown that either the selective disruption of myelin or the targeted functional inhibition of the aforementioned myelin proteins within either the developing and adult avian or mammalian spinal cord can facilitate functional axonal sprouting and/or regeneration. [10][11][12][13][14][15][16] To reduce transiently the axonal growth inhibition activity associated with CNS myelin, we have developed an immunological intraspinal infusion protocol. 17 The immunological process is activated by infusing a myelinspecific IgG antibody to an outer cell surface myelinspecific epitope (eg anti-galactocerebroside or GalC) that has a high affinity for activating the accompanying infusion of serum complement.…”
Section: Introductionmentioning
confidence: 99%
“…Only when combined will these two reagents selectively target CNS myelin to focally demyelinate an injured spinal cord region in a concentration-dependent, diffusion-limited manner. 11,12,14,17,18 When applied to the embryonic chick spinal cord, prior to transection of the cord, 12,17 this treatment suppressed CNS myelin development and extended the normal permissive period for axonal regeneration and functional recovery to later stages of development. 12,17 In the mature spinal cord of posthatchling birds, the same immunological protocol transiently demyelinates *Correspondence: JK Dyer, International Collaboration on Repair Discoveries (ICORD), University of British Columbia, 6270 University Boulevard, Vancouver, BC, Canada V6T 1Z4 and disrupts compact myelin, thereby facilitating some functional axonal regeneration of axotomized avian brainstem-spinal neurons, albeit at a reduced level of repair when compared to the injured developing spinal cord.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations